Prime minister decree No. 2509 of the year 2016 amending some provisions of the executive regulations of the law on protection of competition and prohibition monopolistic practices promulgated by Prime minister decree No. 1316 of the year 2005 / Translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Serial No. 46/2016